2018
DOI: 10.1039/c8cc01779d
|View full text |Cite
|
Sign up to set email alerts
|

An efficient non-fullerene acceptor based on central and peripheral naphthalene diimides

Abstract: Through the coupling of central and terminal naphthalene diimide functionalities, a unique non-fullerene electron acceptor, coded as N10, was designed, synthesized, characterized and applied in solution-processable bulk-heterojunction devices. The target N10 displayed good solubility, excellent thermal stability and energy levels complementing those of the conventional donor polymer poly(3-hexyl thiophene) (P3HT). An excellent power conversion efficiency of 7.65% was obtained in simple BHJ devices (P3HT : N10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 24 publications
0
9
0
1
Order By: Relevance
“…Aryl imides are an important class of materials and have found extensive use in organic electronic applications. These building blocks are routinely incorporated into both molecular and polymeric designs typically for their electron deficient character and self-assembly properties. Among them, the rylene-based imides, perylene and naphthalene diimide (PDI, NDI, respectively), have found great success as electron transporting materials in organic field-effect transistors (OFETs) and organic solar cells (OSCs). Until recently, N -(alkyl)­benzothioxanthene-3,4-dicarboximide (BTXI), a sulfur containing rylene imide dye used in bioimaging , and for its antitumor activity, had not been considered as a building block for use in organic electronics. Cabanetos et al demonstrated an efficient selective bromination of the BTXI dye that shows excellent compatibility among commonly used palladium catalyzed C–C bond forming reactions including Stille, Suzuki, and Sonagashira, as well as the atom economical direct (hetero)­arylation (DHA) …”
Section: Introductionmentioning
confidence: 99%
“…Aryl imides are an important class of materials and have found extensive use in organic electronic applications. These building blocks are routinely incorporated into both molecular and polymeric designs typically for their electron deficient character and self-assembly properties. Among them, the rylene-based imides, perylene and naphthalene diimide (PDI, NDI, respectively), have found great success as electron transporting materials in organic field-effect transistors (OFETs) and organic solar cells (OSCs). Until recently, N -(alkyl)­benzothioxanthene-3,4-dicarboximide (BTXI), a sulfur containing rylene imide dye used in bioimaging , and for its antitumor activity, had not been considered as a building block for use in organic electronics. Cabanetos et al demonstrated an efficient selective bromination of the BTXI dye that shows excellent compatibility among commonly used palladium catalyzed C–C bond forming reactions including Stille, Suzuki, and Sonagashira, as well as the atom economical direct (hetero)­arylation (DHA) …”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of required starting materials such as 2‐Br‐th‐NDI ( 1 ) [24c] and 4‐ethynyl‐N,N‐diphenylaniline (TPAA) ( 2 ) [26] were achieved by literature reported methods (Scheme 1). NDI‐TPA‐1 to NDI‐TPA‐6 were synthesized according to previous literature reports [11–18] .…”
Section: Resultsmentioning
confidence: 99%
“…lipophilic, hydrophilic, alkoxy, aliphatic with terminal thiol groups, and polyethylene glycol, at imide positions enhances the solubility of a proposed target, a result that is of great significance to generate excellent pristine and blend films of the proposed target material without crystallisation. [79][80][81][82] Therefore, it is timely to review the literature of ETL materials based on NDI functionality and to correlate the structural features with the device performance in order to determine useful design concepts to advance the area. This review provides the current state-of-the-art in the field of ETL materials, both polymers and small molecules, comprising NDI functionality for PSCs and describes structure-property relationships.…”
Section: Ndi-based Electron Transport Layer Materialsmentioning
confidence: 99%